On the Practical Use of Immersive Virtual Reality for Rehabilitation of Intimate Partner Violence Perpetrators in Prison - Barnes, Nicolas; Sanchez-Vives, Maria V.; Johnston, Tania (Frontiers in Psychology, 2022)
Virtual reality allows the user to be immersed in environments in which to experience situations and social interactions from different perspectives by means of virtual embodiment. In the context of rehabilitation of violent behaviours, a participant could experience a virtual violent confrontation from different perspectives, including that of the victim and the bystanders. This approach and other virtual scenes can be used as a tool found to be useful for rehabilitation of intimate partner violence perpetrators, through the improvement of their empathic skills or the training in non-violent responses. In this Perspective, we revise and discuss the use of such tools in a prison environment for the rehabilitation of intimate partner violence perpetrators with a particular focus on practical aspects based on our experience.